The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s10103-017-2157-2
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of a laser fluorescence device and digital radiography in detecting approximal caries lesions in posterior permanent teeth: an in vivo study

Abstract: The aim of this in vivo study was to test the diagnostic accuracy of a pen-type laser fluorescence (LFpen) device in detecting approximal caries lesions, in posterior permanent teeth, at the cavitation and non-cavitation thresholds, and compare it with that of digital bitewing radiography. Thirty patients (aged 18–37), who attended the Faculty of Dentistry at Damascus University for a dental examination, were consecutively screened. Ninety approximal surfaces of posterior permanent teeth without frank cavitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
(28 reference statements)
4
22
2
1
Order By: Relevance
“…Such discrepancies could be explained by the subjectivity of the BW examination, which depends on the examiner's experience and skills, in addition to other factors. Furthermore, the use of digital radiography has been reported for permanent teeth, with very few studies on primary teeth. Therefore, the data herein cannot be compared with studies performed with permanent teeth.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Such discrepancies could be explained by the subjectivity of the BW examination, which depends on the examiner's experience and skills, in addition to other factors. Furthermore, the use of digital radiography has been reported for permanent teeth, with very few studies on primary teeth. Therefore, the data herein cannot be compared with studies performed with permanent teeth.…”
Section: Discussionmentioning
confidence: 89%
“…Studies on permanent teeth showed different results when BW and LFpen were compared to those obtained for primary teeth. An in vitro study of permanent teeth revealed that LFpen performed better than the radiographic method. LFpen also presented higher accuracy in detecting both enamel and dentin carious lesions (D1 threshold) than BW for permanent teeth.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations